2014
DOI: 10.1248/bpb.b13-00972
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effects of 5-Fluorouracil and Gambogenic Acid on A549 Cells: Activation of Cell Death Caused by Apoptotic and Necroptotic Mechanisms <i>via</i> the ROS-Mitochondria Pathway

Abstract: 5-Fluorouracil (5-FUIn conclusion, in addition to the activation of caspase-dependent apoptosis, the combination of GNA and 5-FU might also cause cell death of A549 cells by activating caspase-independent necroptosis. These mechanisms may be due to the toxicity of targeted toxin to mitochondria via the mitochondrial pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 27 publications
0
34
0
Order By: Relevance
“…This is a common phenomenon in today’s chemotherapy with widely spread drug resistance effects from tumors. Most treatments using single anticancer drugs over time have very limited therapeutic efficacy40 due to the drug resistance effect. It is well known that tumor cells exposed to chemotherapeutic agents over time may develop, both in vivo and in vitro , a multidrug resistant (MDR) phenotype, which is generally associated with over-expression of P-glycoprotein (P-gp), the family of multidrug resistance-associated proteins (MRPs) and lung resistance-related protein (LRP)41.…”
Section: Resultsmentioning
confidence: 99%
“…This is a common phenomenon in today’s chemotherapy with widely spread drug resistance effects from tumors. Most treatments using single anticancer drugs over time have very limited therapeutic efficacy40 due to the drug resistance effect. It is well known that tumor cells exposed to chemotherapeutic agents over time may develop, both in vivo and in vitro , a multidrug resistant (MDR) phenotype, which is generally associated with over-expression of P-glycoprotein (P-gp), the family of multidrug resistance-associated proteins (MRPs) and lung resistance-related protein (LRP)41.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies reported about natural active compound can induce apoptosis and cell cycle arrest in human lung cancer (Peng et al, 2016;Su et al, 2014). Dysregulation of cell proliferation, together with inhibition of the apoptosis pathway, is associated with tumorigenesis (Evan and Vousden, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The FLIP L protein can also block the recruitment of caspase-8 to DISC, suppressing death receptor-mediated apoptosis (38). Previous studies showed that GA could markedly sensitize chemotherapeutic drug-induced cell death in a range of cancer cells (6,(39)(40)(41). Therefore, based on these studies, this study examined whether GA-induced cFLIP L downregulation could increase the sensitivity to the death ligands, including TRAIL, TNF-α and FasL in human renal cancer cells.…”
Section: Discussionmentioning
confidence: 99%